Evaluasi Efektivitas Demonstrasi Plot Teknologi Produksi Benih Biji Bawang Merah (True Seed of Shallot) dalam Peningkatan Pengetahuan dan Keterampilan Petani di Kelompok Tani Wana Tani Desa Mutisari, Kecamatan Watumalang, Kabupaten Wonosobo - Wibowo, Arif Puji; Arbian, Wafiq Nur (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2025)
The availability of quality shallot seeds is a major constraint in the development of this strategic commodity in Indonesia, particularly Central Java. A deficit of 82.2% in quality seeds leads farmers to rely on consumption bulbs or imports. True Seed of Shallot (TSS) technology emerges as a promising innovation to address this issue, offering advantages such as high productivity, efficiency, and longer storage life. This study aimed to evaluate the effectiveness of a demonstration plot (demplot) for TSS production technology in enhancing farmer knowledge and skills. The study employed a pre-evaluation and post-evaluation design with 20 members of the Sumber Makmur Farmer Group in Mutisari Village, Watumalang, Wonosobo. Data were collected via questionnaires and analyzed by calculating program effectiveness and skill change effectiveness percentages. Results showed a total pre-evaluation score of 344 and a post-evaluation score of 597. Based on calculations, program effectiveness reached 99.5% and skill change effectiveness was 98.83%. According to the assessment criteria, this demplot was categorized as